1995
DOI: 10.1177/001872679504801106
|View full text |Cite
|
Sign up to set email alerts
|

Work and Commitment Among Young Professionals: A Study of Male and Female Dentists

Abstract: This research examines gender differences in personal characteristics, work experiences, work attitudes, and professional commitment for a group of young (age < 45) dentists. While males and females had similar work attitudes, they differed in work experience -males worked more hours, saw more patients, and earned higher incomes. Males had higher scores on affective and behavioral professional commitment measures than did females, but the gender difference was significant only for behavioral commitment. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 39 publications
5
51
1
6
Order By: Relevance
“…This was contrary to expectations (Colarelli & Bishop, 1990;Kaldenberg, Becker, & Zvonkovic, 1995). Further studies are required before any recommendations can be made regarding the importance of personal characteristics in understanding professional commitment.…”
Section: Levels Of Commitmentcontrasting
confidence: 62%
“…This was contrary to expectations (Colarelli & Bishop, 1990;Kaldenberg, Becker, & Zvonkovic, 1995). Further studies are required before any recommendations can be made regarding the importance of personal characteristics in understanding professional commitment.…”
Section: Levels Of Commitmentcontrasting
confidence: 62%
“…On the other hand, Women have less opportunities with other organizations and overcome more barriers to get where they are, thus they are more likely to be committed to their organizations. Nevertheless, there are studies that report greater organizational commitment by men, even after controlling for job-related factors (Kaldenberg et al, 1995).…”
Section: The Relationship Between Pc and Ocmentioning
confidence: 99%
“…On personal characteristics, some earlier research has suggested those women and especially those who work part time and married women with children will have lower levels of commitment to their work than men. One set of studies reports greater organizational commitment by men (Arana et al, 1986;Baird et al, 1998;DoddMcCue and Wright, 1996;Kaldenberg et al, 1995). However, in some of these studies, the bivariate results lose their significance once job-related factors are entered as controls (Arana et al, 1986;Dodd-McCue and Wright, 1996).…”
Section: The Relationship Between Pc and Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…In the view of Chughtai & Zafar (2006), marital status has emerged as a consistent predictor of organizational commitment. Kalenberg et al (1995), in their study of dentists, found that marriage is related to commitment. However, this relationship was only significant for behavioral commitment among males.…”
Section: Studies Related To Marital Status and Organizational Commitmentmentioning
confidence: 99%